Hybrid Aqueous Batteries: Atomic Engineering Catalyzed MnO2 Electrolysis Kinetics for a Hybrid Aqueous Battery with High Power and Energy Density (Adv. Mater. 25/2020). Issue 25 (24th June 2020) - Chao, Dongliang; Ye, Chao; Xie, Fangxi; Zhou, Wanhai; Zhang, Qinghua; Gu, Qinfen; Davey, Kenneth; Gu, Lin; Qiao, Shi‐Zhang
Abstract : A paradigm high‐rate and high‐voltage affordable Zn–Mn hybrid aqueous battery (HAB) is constructed by Shi‐Zhang Qiao and co‐workers (article number 2001894 ). The fairytale depicts a cowherd (the Mn cathode) on the ground, and the weaving girl (the Zn anode) on the moon, who are separated (by a membrane). They can only express their love by the media of H + and OH −, which produce a streamlet and powers the moon (lamp bulb). The carrier pigeon (Ni) serves as a catalyst to speed‐up the process (reaction).